Energy Development Status and Developing Focus of Varied Regions in China - Gao Dan (《中国工程科学》杂志社, 2021)
China has a vast territory, so the energy resource endowments of different regions in the country are significantly varied. Promoting regional energy revolution based on local conditions is an effective way to break the bottlenecks that restrict China’s energy development. This study analyzes the current situation of energy development from the aspects of energy production, consumption, and distribution, and investigates the differences regarding energy consumption intensity and the driving force for energy consumption growth in the core regions (i.e., the Beijing–Tianjin–Hebei region, Yangtze River Delta, Pearl River Delta, old industrial bases, the Central China, energy-rich areas, and Southwest China). The medium- and long-term energy development trends and strategic focuses of these regions by 2035 are analyzed. Specifically, the Beijing–Tianjin–Hebei region should focus on the coordinated development of energy, economy, and environment; an energy system with regional linkage should be formed and optimized in the Yangtze River Delta; the Pearl River Delta can strive to build itself as a clean energy production, storage, and transportation base; economic transformation should be promoted in the old industrial bases through value increment and diversification of energy resources; Central China should establish itself as an integrated energy hub; the energy-rich areas should build itself as a green and sustainable energy security base; and clean energy consumption should be encouraged in Southwest China. To coordinate energy development in various regions, China should fully consider the significant differences in local conditions, promote social development and ecologicalprotection with the regional energy revolution, and encourage regional cooperation in energy.